As histórias em quadrinhos de Maria Erótica (1979-1981) de Claudio Seto: visões carnavalizantes durante a ditadura militar - Santos, Leandro Luiz dos (2020)
This academic work aims to analyze the stories of the magazine “Maria Erótica” created by Claudio Seto (1944-2008) and published by the publishing house Grafipar, in Curitiba, between the second half of 1979 and the beginning of the 1980s. The analysis was developed according the concept of “carnivalization” by the Russian philosopher and linguist Mikhail Bakhtin (1895-1975), in which humor and the unusual are used as a way of contesting the current hierarchy and order. This concept was applied in the 18 stories of the sample based on the premise that erotic comics - even if unintentionally - violated the morals of the conservative society that supported the implantation and maintenance of the Brazilian military dictatorship (1964-1985). At that time, erotic comics were also the target of censorship, mainly because pornography was prohibited in the country. The protagonist Maria Erótica - created in 1969 and considered one of Seto's great creations - proves to be, from the analysis, an object of the male fetish. In most sexual scenes, the initiative comes from men and not from Maria - sexual harassment and abuse appear recurrently in most of the stories analyzed. The protagonist only surrenders to sexual interludes in the world of fantasy, since in reality she proves to be moral and prudish. Based on these findings, Maria Erótica is seen as a reflection of the Brazilian patriarchal society that does not allow full sexual freedom for women. Other protagonists of international erotic comics from the same period are controversial regarding women's sexual liberation - such as Barbarella, by JeanClaude Forest (1930-1998). In the dissertation, in parallel to the development of the analyzes, Claudio Seto's biographical aspects are approached - especially with regard to his comic production - based on reports from co-workers and family members. Seto, grandson of Japanese immigrants, has great importance in the context of Brazilian comics for being considered one of the introductors of the manga style in the country.